Turmeric Extraction (Curcuma Longa L) Using The Reflux Method And Characterization (Universitas Negeri Semarang, 2022)
Turmeric (Curcuma longa L) is one of the many spices that grow on the Asian continent, especially Southeast and South Asia, which can be utilized to its full potential, especially the antioxidant compounds contained in curcuminoids. This study aims to determine the effect of different forms of turmeric, powder and fresh, on the extraction using the reflux extraction method and antioxidant activity using the DPPH method (2,2-Diphenyl-1-PicrylHydrazyl). The reflux extraction process was carried out using distilled water with three variations of sample forms, turmeric powder, fresh turmeric (grated turmeric and pieces of turmeric) with a solute/solvent ratio (w/v) (1:5). The viscous extract in the form of a paste was obtained after the distillation process and solvent evaporation. The best extracts and essential oils obtained were extracts from powdered turmeric samples with yields of 8.28 (% w/w) and essential oils of 0.44 g, which were clearer than the other two samples. The analysis showed that the sample of turmeric with the highest antioxidant activity was a sample of freshly grated turmeric with an IC50 value of 114.7 ppm with a moderate level of antioxidant activity. The cut turmeric sample has an IC50 value of 158.3 ppm, which is included in the weak antioxidant activity. The powdered turmeric sample has an IC50 value of 134.1 ppm with moderate strength.